Development of high-modulus water swellable elastomer composite for oil-field applications - Han, Dingzhi (2015)
A novel reactive swellable elastomeric composite made by compounding hydrogenated acrylonitrile butadiene rubber (HNBR) with magnesium oxide (MgO) is described in this study. Conventional water swellable elastomers are made by compounding elastomer with super-absorbent polymers (SAPs) which, upon exposure to water, absorb water and hold water in its liquid state. As a result, the stiffness of the conventional water swellable elastomers decrease as they swell due to dilution of the stiff elastomeric matrix by fluid water. The HNBR-MgO composite behaves differently as most of the water absorbed reacts with MgO to form solid magnesium hydroxide (Mg(OH)2). Therefore, instead of a reduction in modulus with swelling, the HNBR-MgO composites were found to swell and stiffen with hydration. Five mixing ratio of HNBR and 2μm MgO (14 vol%, 20 vol%, 28 vol%, 33 vol% and 40 vol% of MgO) were studied. Moreover, three particle sizes of MgO (2 μm, 5 μm and 10 μm) were also mixed with HNBR at 40 vol%. The influence of filler content and filler size on the swelling and stiffening of this novel composite was investigated. Increasing the filler content of HNBR-MgO composites from 14 vol% to 40 vol% yielded swelling of about 25 vol% to 100 vol% while the modulus of the hydrated compounds increased from about 15 MPa to 80 MPa for the hydrated coumpounds. On the other hand, increasing the MgO particle size from 2 μm to 10 μm yields similar swelling across the compounds but the modulus decreased from 80 MPa to 11 MPa. Both swelling and increase in modulus are attributed to the processes involved in the hydration of MgO to form Mg(OH)2. Volume increase with hydration of the composite is caused by the bonding of water to MgO as well as some amount of free water which, after drying, leave behind unfilled pores within the filler structures, causing a ii larger than expected volume increase. Modulus increase is due to the increase in effective filler content, reduction in filler size as well as increase in filler aspect ratio after hydration of MgO. Phenomenological models to predict the change in modulus with filler content and with hydration were proposed via modifying the Guth and Gold equation and the Halpin-Tsai equation. The Halpin-Tsai model was found to represent the experimental data fairly well.